LNMAT1 promotes lymphatic metastasis of bladder cancer via CCL2 dependent macrophage recruitment - Changhao Chen (Nature Portfolio, 2018)
Mechanism of lymph node (LN) metastasis induced by tumor associated macrophages (TAMs) remains unclear. Here they demonstrate that a long noncoding RNA LNMAT1 promotes LN metastasis of bladder cancer via recruitment of TAMs through epigenetic regulation of CCL2 expression.